2023
DOI: 10.2337/db22-0575
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrate and Corresponding Gut Microbiota Prevent Cardiac Dysfunction in Obese Mice

Abstract: Impaired heart function can develop in diabetic individuals in the absence of coronary artery disease or hypertension, suggesting mechanisms beyond hypertension/increased afterload contribute to diabetic cardiomyopathy. Identifying therapeutic approaches that improve glycemia and prevent cardiovascular disease are clearly required for clinical management of diabetes-related comorbidities. Since intestinal bacteria are important for metabolism of nitrate, we examined if dietary nitrate and fecal microbial trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In addition to pharmaceutical interventions, the intake of dietary nitrate (NO 3 − ) through beetroot juice has been shown to enhance exercise capacity in patients with HFpEF [239] and increase the maximum rate of oxygen consumption during exercise in patients with diabetes [240]. Rodent studies demonstrated the beneficial effect of dietary nitrate on HFD-induced liver steatosis through the modulation of microbiota [241] and cardiomyopathy [242] in mice. These findings suggest that dietary nitrate could be a therapeutic option for diabetic cardiomyopathy through the modulation of gut microbiota.…”
Section: Targeting Gut Homeostasismentioning
confidence: 99%
“…In addition to pharmaceutical interventions, the intake of dietary nitrate (NO 3 − ) through beetroot juice has been shown to enhance exercise capacity in patients with HFpEF [239] and increase the maximum rate of oxygen consumption during exercise in patients with diabetes [240]. Rodent studies demonstrated the beneficial effect of dietary nitrate on HFD-induced liver steatosis through the modulation of microbiota [241] and cardiomyopathy [242] in mice. These findings suggest that dietary nitrate could be a therapeutic option for diabetic cardiomyopathy through the modulation of gut microbiota.…”
Section: Targeting Gut Homeostasismentioning
confidence: 99%